1997
DOI: 10.1042/bj3260311
|View full text |Cite
|
Sign up to set email alerts
|

A specific distal promoter controls γ-glutamyl transpeptidase gene expression in undifferentiated rat transformed liver cells

Abstract: In rat undifferentiated hepatoma cells, the gamma-glutamyl transpeptidase (GGT) gene is transcribed into a 2.3 and a 2.6 kb mRNA which, in contrast with other rat GGT transcripts, are not detected in more differentiated liver cells or adult tissues. Analysis of the cDNA sequences obtained from H5 hepatoma cells reveals that these two transcripts differ from other GGT mRNAs by a 312-nt unique untranslated leader sequence; this sequence maps on the gene in a single exon 10 kb upstream from the GGT promoter IV tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…mRNA V was first identified in rat undifferentiated hepatoma H5 and HTC cells [30]. Our results here show that GGT mRNA V (V-2) was expressed predominantly in rat lung, spleen, ovary, testicle, and embryo and to a lesser extent in liver, kidney, and brain but not in heart and thymus (Fig.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…mRNA V was first identified in rat undifferentiated hepatoma H5 and HTC cells [30]. Our results here show that GGT mRNA V (V-2) was expressed predominantly in rat lung, spleen, ovary, testicle, and embryo and to a lesser extent in liver, kidney, and brain but not in heart and thymus (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…In this cell line, we observed that the AP-1/ hepatocyte nuclear factor (HNF) 3 overlapping site located between −27 and −48, which was reported to be essential for the basal expression of GGT mRNA in undifferentiated hepatoma H5 cells [30], is not involved in the basal activity of GP5. HNF3 is a member of the forkhead winged helix family, and its function is often controlled by regulatory factors which have binding sites overlapping with HNF3 motif [44].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations